Phytosociology of aquilaria malaccensis lamk. And its communities from a tropical forest reserve in Peninsular Malaysia - Razak, S.A.; Haron, N.W. (2015)
A phytosociological study on the floristic and vegetation communities of Aquilaria malaccensis was carried out in Sungai Udang Forest Reserve, Malacca, Malaysia. The main objectives of this study were to identify, characterize and classify the Aquilaria malaccensis communities which were naturally distributed in the Sungai Udang Forest Reserve. A total of 25 plots (40 m x 20 m) in size were constructed according to the line transect method. The vegetation sampling and data analysis were done. A total of 80 species belonging to 79 genera and 40 families were found from all the 25 plots in Sungai Udang Forest Reserve. The most abundant family was the Euphorbiaceae with 220 individual trees, followed by Myrtaceae and Anacardiaceae representing 212 and 197 individual trees, respectively. A community which was Aquilaria malaccensis - Artocarpus rigidus community with two new sub-community known as Palaquium gutta sub-community and Barringtonia racemosa sub-community were identified on the basis of statistical and phytosociological analyses. These community and sub-community also showed preference on different geographical and environmental factors such as soils and local relief. This study is useful in providing more information on the growth response of the mixed dipterocarp forest in the development of proper forest management.